2011
DOI: 10.1525/bio.2011.61.10.8
|View full text |Cite
|
Sign up to set email alerts
|

Interactions among Foundation Species and Their Consequences for Community Organization, Biodiversity, and Conservation

Abstract: Foundation species create complex habitats in which associated organisms find refuge from biological and physical stress; these foundation species are thus fundamental to the structure and resilience of terrestrial and marine ecosystems. In the present article, we develop an approach to understanding foundation species' effects in communities that are maintained not by a single foundation species, as has been the focus of research to date, but by multiple, co-occurring foundation species. Using examples from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
239
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 258 publications
(259 citation statements)
references
References 58 publications
6
239
0
1
Order By: Relevance
“…All but one of the organizations surveyed plant propagules at restoration sites with, rather than without, spacing. This focus on planting designs that minimize the potential for negative interactions among outplants has persisted despite over two decades of ecological research showing positive interactions (e.g., mutualisms, facilitations) play a critical role in controlling the structure and function of ecological communities, especially under conditions of elevated physical stress (30)(31)(32) where neighboring plants can ameliorate physical stress for each other, including anoxic stress and wave-induced erosion stress in seagrasses, marshes, and mangroves (33)(34)(35). Indeed, a global metaanalysis of over 700 studies revealed that positive species interactions are most important for organism success and community persistence and recovery as physical stress increases (32), a scenario that mirrors intense abiotic stress conditions that are found on bare substrate after a coastal ecosystem has been degraded, which then is often targeted for restoration efforts (29,31).…”
Section: Significancementioning
confidence: 99%
“…All but one of the organizations surveyed plant propagules at restoration sites with, rather than without, spacing. This focus on planting designs that minimize the potential for negative interactions among outplants has persisted despite over two decades of ecological research showing positive interactions (e.g., mutualisms, facilitations) play a critical role in controlling the structure and function of ecological communities, especially under conditions of elevated physical stress (30)(31)(32) where neighboring plants can ameliorate physical stress for each other, including anoxic stress and wave-induced erosion stress in seagrasses, marshes, and mangroves (33)(34)(35). Indeed, a global metaanalysis of over 700 studies revealed that positive species interactions are most important for organism success and community persistence and recovery as physical stress increases (32), a scenario that mirrors intense abiotic stress conditions that are found on bare substrate after a coastal ecosystem has been degraded, which then is often targeted for restoration efforts (29,31).…”
Section: Significancementioning
confidence: 99%
“…Habitat-forming species (HFS) can be considered 'ecological engineers' (sensu Jones et al, 1994), as they directly and indirectly alter environmental conditions for other organisms (Thomsen et al, 2010;Angelini et al, 2011). Within benthic marine ecosystems, HFS play a key role in determining the structure of proximal communities by influencing biological and physiological factors and providing key resources (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Foundation species are those structurally dominant members of ecological communities that stabilize and mediate ecological processes (Dayton 1972, Ellison et al 2005. They build habitat and facilitate community assembly, provide critical ecosystem services and, in some systems, are thought to confer ecological resilience to disturbances like wildfire and resistance to biological invasions (Prevey et al 2010, Angelini et al 2011. Being common, foundation species are often overlooked as being at conservation risk but, as with other less prominent members of ecological communities, they may also be threatened from land use change, biological invasions, and over-exploitation (Gaston and Fuller 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the facilitative role that foundation species play in community assembly (Gaston and Fuller 2007) has motivated their use in ecosystem restoration (Byers et al 2006, Gomez-Aparicio 2009, Angelini et al 2011). The so-called ''neighbor effects'' documented in many plant communities dominated by foundation species (see review by Gomez-Aparicio 2009) have led to a paradigm shift in terrestrial restoration in which emphasis is increasingly on maintaining existing native vegetation or replanting desired foundation species for facilitation rather than on removal of competitive invaders (Gomez-Aparicio 2009).…”
Section: Introductionmentioning
confidence: 99%